2018
DOI: 10.1016/j.semarthrit.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of measurement properties of patient reported outcome measures in psoriatic arthritis: A GRAPPA-OMERACT initiative

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ Takedown If you consider content in White Rose Research Online to be in breach of UK law, please notify us by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 62 publications
0
47
0
2
Order By: Relevance
“…In recent years, the rheumatology community has witnessed an intense search for sensitive and valid instruments that capture those clinical aspects related to disease activity, as well as those linked to the response to the scheduled treatments, along with other instruments, more focused on the experiences and perceptions lived by PsA patients [3][4][5][6]15]. Despite this intense search, there is a remarkable mismatch between the results derived from the instruments for measuring disease activity (e.g., DAPSA), or those that assess the treatment objectives (e.g., MDA), and the PROMs (e.g., pain, fatigue, PsAID).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rheumatology community has witnessed an intense search for sensitive and valid instruments that capture those clinical aspects related to disease activity, as well as those linked to the response to the scheduled treatments, along with other instruments, more focused on the experiences and perceptions lived by PsA patients [3][4][5][6]15]. Despite this intense search, there is a remarkable mismatch between the results derived from the instruments for measuring disease activity (e.g., DAPSA), or those that assess the treatment objectives (e.g., MDA), and the PROMs (e.g., pain, fatigue, PsAID).…”
Section: Discussionmentioning
confidence: 99%
“…However, several of the tools have some evidence for good measurement properties in PsA (52). To optimize treatment strategies, clinicians and patients need insight into how pain mechanisms, disease activity, and sociodemographic and psychological factors interact and contribute to the overall prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the COS domains were pragmatically chosen, since a recommended set of COS instruments is not yet endorsed by OMERACT. However, several of the tools have some evidence for good measurement properties in PsA (52).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical remission characteristics of the study population are shown in Table 2 In recent years, the rheumatology community has witnessed an intense search for sensitive and valid instruments that capture those clinical aspects related to disease activity, as well as those linked to the response to the scheduled treatments; along with other instruments, more focused on the experiences and perceptions lived by PsA patients [3][4][5][6]15]. Despite this intense search, there is a remarkable mismatch between the results derived from the instruments for measuring disease activity (e.g., DAPSA), or those that assess the treatment objectives (e.g., MDA), and the PROMs (e.g., pain, fatigue, PsAID).…”
Section: Resultsmentioning
confidence: 99%